MAIN CHALLENGES OF LONG-TERM CARE SYSTEM IN EUROPEAN COUNTRIES - Dragićević, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
This paper analyzes the main challenges faced by long-term care (LTC) systems in contemporary European countries. The research focuses on identifying and critically examining the legal, institutional, and financial constraints that affect the accessibility, quality, and sustainability of care services. The aim of the study is to determine the key systemic shortcomings and propose directions for their resolution through a comparative analysis of relevant policies, organizational models, and existing literature. Special attention is devoted to issues such as the normative status of LTC as a social right, the position of informal caregivers (with an emphasis on gender dimensions), the working conditions of formal care workers, fragmentation of responsibilities, and the structure and redistributive effects of financing models. The findings reveal that despite certain normative progress within the EU framework, most countries still pursue care policies characterized by selectivity, insufficient institutional support, territorial disparities, and excessive reliance on unpaid family care. Moreover, financial unsustainability and a lack of professionalized care workforce are identified as serious threats to the future of these systems. The conclusion highlights the need for a comprehensive reform encompassing the universalization of the right to care, integration of social and health services, professionalization and improved working conditions of caregivers, as well as the development of a fairly structured and fiscally sustainable financing model. The challenges identified in this study indicate that the transformation of long-term care systems is not only a social and economic imperative but also a normative and civilizational one.